2019
DOI: 10.1186/s13019-019-0900-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the levels of inflammatory markers after transthoracic device closure of ventricular septal defects in pediatric patients

Abstract: Background Transthoracic device closure of ventricular septal defect (VSD) is widely used in the clinic, especially in China. Changes in inflammatory marker levels after transthoracic device closure of VSD in pediatric patients have not been reported. Methods We retrospectively collected clinical data for 85 pediatric patients in our hospital from September 2017 to January 2018. The patients were divided into two groups according to treatment (device group vs. surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A total of 21 studies were included in the pooled analyses 5,15–19,21–35 . Data were collected for the following timepoints: pre‐CPB, end of CPB, 1 h after CPB, POD 1, POD 2, POD 3, POD 4, and POD 5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 21 studies were included in the pooled analyses 5,15–19,21–35 . Data were collected for the following timepoints: pre‐CPB, end of CPB, 1 h after CPB, POD 1, POD 2, POD 3, POD 4, and POD 5.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 21 studies were included in the pooled analyses. 5,[15][16][17][18][19][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Data were collected for the following timepoints: pre-CPB, end of CPB, 1 h after CPB, POD 1, POD 2, POD 3, POD 4, and POD 5. Figure 1 outlines the study search strategy while Table 1 provides an overview of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2019 report of cardiovascular disease in China indicated that there are roughly 2 million individuals suffering from congenital heart disease (CHD), with over 110,000 pediatric patients undergoing surgical treatment for this condition annually. Given that pediatric patients have a very physiologically limited contractile reserve, they are at a high risk of marked reductions in ventricular performance during cardiac surgery as a consequence of factors such as hypoxia, acidosis, ischemia-reperfusion injury, neurohormone-mediated activation, or systemic inflammation [1, 2]. These risk factors can lead to 3~14% of patients that undergo surgery with cardiopulmonary bypass (CPB) suffering from heart failure or low cardiac output syndrome (LCOS), while these rates can be as high as 25% in pediatric patients and are linked to a 15-fold rise in morbidity and mortality following surgical treatment of CHD [35].…”
Section: Introductionmentioning
confidence: 99%